Donors of Longmen: Faith, Politics, and Patronage in Medieval Chinese Buddhist Sculpture, Amy McNair - Kieschnick, John (Buddhist Studies Review, 2007)
Donors of Longmen: Faith, Politics, and Patronage in Medieval Chinese Buddhist Sculpture, Amy McNair (Honolulu, HI: University of Hawai’i Press, 2007), 230 pp., $52/£33.50, ISBN 0-8248-2994-8